Percutaneous electrical stimulation in strength training: an update - Sanchez, B. R.; Puche, P. P.; Gonzalez-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2006)
Numerous studies have used percutaneous electrical stimulation (PES) in the context of training programs to develop strength and physical performance in healthy populations (sedentary or trained). Significant increases in muscle and fiber cross-sectional area, isokinetic peak torque, maximal isometric and dynamic strength, and motor performance skills have been found after PES training. These strength gains are explained on the basis of the characteristics of PES motor units (MUs) recruitment: (a) a continuous and exhausting contractile activity in the same pool of MUs during the entire exercise period, (b) a supramaximal temporal recruitment imposed by the high frequency chosen (up to 40 Hz), and (c) a synchronous recruitment of neighboring fibers. The PES training method is complementary to voluntary training, mainly because the application of PES causes an unconventional spatial recruitment of MUs that, depending on the muscular topography, may entail the preferential recruitment of the fast-twitch MUs. In addition, the method does not specifically develop elasticity in skeletal muscle, and it must be accompanied by a technical workout.